Do manuscrito ao impresso: tradição discursiva das receitas culinárias - Amaro, Luanna Vaz (2012)
The culinary traditions contained in handwritten recipes from culinary manuscripts and printed are observed and understood by rooted feelings and meanings, from traces of significant events, redeeming or reaffirming an identity, thus making communication between present and past through memory. These events are part of the historic city of joao pessoa, inserted in the manuscripts of the women of this city in the twentieth century. The construction of a cultural identity can be seen even through food. Therefore, it seeks to syncretism evidenced by discursive tradition of recipes that emerge through the culinary traditions, a product of contact between different cultures forming paraibana society. The culinary traditions are kept because they are all the time being reworked in a dynamic process, with time, space and identity. Through culinary manuscripts of the "scriptures feminine" in the form of oral and handwritten reports that emerge as statutes of orality, and legitimates and prints the fugacity of oral text, affirming the triumph of voice and lyrics as memory. Through this practice is also reflected concern about the house and its administration and the relationships between women and society. Through food identifies the habits and customs of each family and society in general. The importance of revenue is present as sources of memories, be they memory of a traditional society, whether of a modernity punctuated by recipes printed newspapers or clippings diverse set in terms of women who begin to leave their world win the world, never forgetting that your most valuable role is the woman who takes care of the house and showing the changes that modernity has to be added in this tradition the emergence of modern apparatus. It is revealed from the records of rhetorical platitudes, the imaginary reasons, the ethos, trends and lexical search of authorship, authenticity image of individual identities while movências point the archetype of every family, every group. Analyzing the symbolism of the manuscripts, scriptures while allowing a vision ethnolinguistic as symbolic play of language whose combination forms the social bond and legitimizes a force of persuasive testimony. By analyzing recipes, handwritten or printed, as a "deed" to be setting an oral text, according zumthor (1993, 1997, 2000, 2005), the discursive traditions of revenues, compared to a text with another produced at different times, according kabatek (2006) and has a story to be told from what they ate according to research by gilberto freyre (1969, 2005), chamber krab (2004, 2006) and (montanari: 2008), on privacy (perrot: 1991, 2007), tradition and custom (hobsbawm: 1997), culture (bhabha: 2007), memory (bosi: 1979, 2003) and textual genres (marcuschi: 2000, 2004, 2008 and possenti, 2002; 2009). All this theoretical basis will point to the choices of recipes from each author of the manuscripts are conditioned by society and culture belong to that particular group, so the food transcends character and physiological points a social, historical, linguistic and cultural. Meals update themselves as motivators signs of individual and collective memory, drawing a large map of the customs, the behavior of households, showing the web of circularity of knowledge and connections to the collective memory of the print.